Conto maravilhoso: uma proposta de ensino a partir dos quatro eixos de integração de Língua Portuguesa na BNCC anos finais do ensino fundamental - Oliveira Filho, Aluizio Moreira de (2023)
In 2020, the entire world population was affected by something unexpected: the new coronavirus pandemic. In the educational field, all institutions, private and public, were forced to think, study and quickly test possibilities to continue carrying out their work from home. Faced with so many challenges, teachers set up improvised studios in a room in the residence, many were faced, for the first time, with the need to be in front of a camera, they learned to use technological resources so that it would be possible to teach classes and, we believe to be the more difficult, interact and follow the student's learning evolution through the remote class. In these comings and goings, the Google Meet platform was discovered, which made virtual contact between students and teachers possible. In a 7th grade class at a private institution, the subject of this study, located in the city of Recife, it was noticed that, when working with the textual genre wonderful tale, added in the annual plan of the series in 2021, the students' interaction increased due to the text itself and its meanings, the freedom to build wonderful narratives and the way in which the collaborative production of wonderful tales through digital tools was proposed. However, we found some slips when working the four axes of integration of the Portuguese language in the BNCC from the textual genre mentioned during the elaboration process, incorporating the technological resources foreseen in the Base in a short time of programmatic classes to present the textual genre proposed. This work is an action-research with bibliographical research and virtual experience that aims, in general, to present a course proposal with the theme "wonderful tale", based on the four axes of integration of the Portuguese Language of the BNCC, for students of the 7th year of elementary school based on the gaps and advances identified in the discussion on gender during remote classes, taught during the pandemic and, more specifically, linking them to the discussions and reflections presented by authors such as Solé (1998), Kleiman (2004), Koch and Elias (2018) who debate the reading axis; Marcuschi (2008, 2010), Guedes (2009), for the textual production axis; Schneuwly and Dolz (2004) discussing orality; Vargas (2011), Abraçado (2020) to endorse the linguistic/semiotic analysis. We believe it is important to bring the concepts of the theory of textual genres from the perspective of Marcuschi (2008), the textual genre short story, discuss the difference between fantastic tale and wonderful tale in the conceptions of Propp (1984) and Reis (2014) and present the definitions about the multimodality and the new textual genres from Marcuschi (2010), Rojo (2012) and Ribeiro (2021) making students recognize the constitutive elements of the chosen textual genre so that they reconstruct the texts in order to produce, as a didactic proposal , an e-book and an audiobook.